First aid Q&A for the USMLE Step 2 CK - Le, Tao (McGraw-Hill Medical, 2010)
Presents a question and answer review for the USMLE Step 2 CK. This title includes 1,000 board-format questions correlated to chapters from "First Aid for the USMLE Step 2 CK". It also includes one complete board-simulating examination for comprehensive self-assessment.